Integration of Islam and Science: Study of Two Science Pesantrens (Trensain) in Jombang and Sragen - Munadi, Muhammad (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2016)
This study reviewed about the implementation of integrating Islam and science in curriculum practice at two science Pesantrens both in Sragen and Jombang. The research method used in this study was documents study which focused on the detail curriculum existed in both Science Pesantrens (Trensain) Tebuireng Jombang and Sragen. The documents were taken from their Pesantren Web. Data analysis was conducted by using descriptive qualitative analysis. The result of the study shows that education in those Sragen and Jombang Science Pesantren (Trensain) is a form of creativity in the framework of integration of Islam and natural science. Further, it combines models between school institution and Pesantren. Their integration framework refers to normative power (Quran and Sunnah), philosophical power, strengthening the mastery of natural science, and power of foreign language mastery.